2022
DOI: 10.1055/a-1853-9889
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride-Glucose Index and the Prognosis of Patients with Acute Ischemic Stroke: A Meta-Analysis

Abstract: A higher triglyceride-glucose (TyG) index has been related to an increased incidence of stroke in community population. A meta-analysis was performed to evaluate the association between TyG index and prognosis in patients with acute ischemic stroke (IS). Observational studies, which evaluated the influence of TyG index on functional outcome and mortality in patients with acute IS were retrieved by search the Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
2
1
0
Order By: Relevance
“…Many previous studies have shown an association between a higher TyG index and an increased incidence of atherosclerosis, intima media thickness of common carotid artery, unstable carotid plaque, hypertension, arterial stiffness, and cardiovascular disease [10][11][12][13]. As expected, a plenty of evidences proved that TyG index was independently associated with the occurrence of stroke, and a higher TyG index was also a predictor of all-cause mortality and poor outcomes in patients with acute ischemic stroke [14][15][16][17].…”
Section: Introductionsupporting
confidence: 55%
“…Many previous studies have shown an association between a higher TyG index and an increased incidence of atherosclerosis, intima media thickness of common carotid artery, unstable carotid plaque, hypertension, arterial stiffness, and cardiovascular disease [10][11][12][13]. As expected, a plenty of evidences proved that TyG index was independently associated with the occurrence of stroke, and a higher TyG index was also a predictor of all-cause mortality and poor outcomes in patients with acute ischemic stroke [14][15][16][17].…”
Section: Introductionsupporting
confidence: 55%
“…A higher TyG index was linked with an increased risk of early neurological deterioration and a decreased early neurological improvement in AIS patients with IV thrombolytic therapy. Particularly, the TyG index was closely correlated with early neurological deterioration in patients with subcortical infarcts near the middle cerebral artery [30]. It was reported that higher TyG index was related to increased mortality and poorer functional outcomes in both diabetic and non-diabetic patients [31], which con rmed our observation in this study.…”
Section: Multifactor Logistic Regression Analysissupporting
confidence: 89%
“…5 The various studies have concluded that the higher triglyceride index is an important predictor of mortality and outcome of acute ischemic stroke. 6 Thus, the present study was undertaken to elucidate the association between TyG index in type 2 diabetes mellitus patients and acute ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%